Management of Traumatic Soft Tissue Injuries of the Face - Cho, Daniel Y.; Willborg, Brooke E.; Lu, G. Nina (Seminars in Plastic Surgery, 2021)
Facial soft tissue injuries encompass a broad spectrum of presentations and often present significant challenges to the craniofacial surgeon. A thorough and systematic approach to these patients is critical to ensure that the patient is stabilized, other injuries identified, and the full extent of the injuries are assessed. Initial management focuses on wound cleaning with irrigation, hemostasis, and debridement of nonviable tissue. Definitive management is dependent on the region of the face involved with special considerations for critical structures such as the globe, lacrimal apparatus, facial nerve, and parotid duct. Following sound surgical principles, these injuries can be managed to maximize both functional and aesthetic outcomes while minimizing complications.
Keywords: facial trauma; soft tissue injury; laceration; facial nerve; parotid duct